Phosphorothioate and cordycepin analogues of 2',5'-oligoadenylate: inhibition of human immunodeficiency virus type 1 reverse transcriptase and infection in vitro. - Montefiori, D C (1989)
Natural antiviral activity can be mediated by the interferon-induced synthesis of 2',5'-oligoadenylates (2-5As) and subsequent RNase L activation by these molecules. Analogues of 2-5A that are biologically active and metabolically stable were synthesized and analyzed for antiviral activity against the human immunodeficiency virus type 1 (HIV-1). Replacement of the 3' hydroxyl group of the adenosine moieties of 2-5A with hydrogen atoms (i.e., cordycepin analogues of 2-5A) converted authentic 2-5A trimer into anti-HIV-1 agents in vitro. These cordycepin analogues of 2-5A also inhibited partially purified HIV-1 reverse transcriptase. Introduction of chirality into the 2',5'-phosphodiester internucleotide linkages or 5'-phosphate moieties of the 2-5A molecule (i.e., phosphorothioate analogues of 2-5A) converted authentic 2-5A into more potent inhibitors of HIV-1 reverse transcriptase. However, these phosphorothioate 2-5As demonstrated little or no anti-HIV-1 activity in vitro. Thus, some analogues of 2-5A may form a class of anti-HIV-1 drugs with possible pleiotropic activities that include activation of latent RNase L and inhibition of reverse transcription.